Etnobotânica, cultivo sustentado, uso terapêutico de plantas medicinais: hábitos culturais de saúde e a qualidade de vida em comunidades quilombolas do Baixo Amazonas - RIBEIRO, Aylla Cristina Sousa (Universidade Federal do Oeste do Pará, 2023)
The health-disease process and its conceptualization follows the historical evolution of humanity, as well as the discussion around cultural habits, being cultures the result of interpersonal experiences and relationships established with the environment i n which they live. Medicinal plants have been part of the human evolutionary process since ancient times, as they have been used as therapeutic resources in different places in the world. In fact, popular knowledge has been increasingly valued due to practical wisdom involving medicinal plants and their applications for therapeutic purposes in the most diverse human communities until the present day. The present research has as general objective the investigation of ethnobotany, sustainable cultivation and the use of medicinal plants in Quilombo communities [Black Communities] in the Lower Amazon region. Our specific objectives are to present which medicinal plants are being used in communities for therapeutic purposes, to investigate the relationship between cultural habits and collective health with the quality of life of Quilombo communities in the Lower Amazon; as well as to investigate possible transpositions of medicinal plants from Africa to the Amazon. We intend to achieve these objectives to answer our scientific question, namely: are ethnobotany, the sustainable cultivation and therapeutic use of medicinal plants by Quilombo communities in the Lower Amazon region are cultural habits that influence and favor the quality of life of its residents? So to achieve this goal, the investigations will be carried out through the collection of information resulting from the narrations of herbalists, faith healers and other people involved with the manipulation of medicinal plants in the Quilombo communities in the region of the headwaters of São Paulo, in the municipality of Óbidos – Pará; in addition we shall expose possible relationships between medicinal plants cultivated in Quilombo territory with African medicinal plants. The methodological trajectory of this study is based on bibliographic research and the oral history of community members on the subject. The research intends to achieve results that demonstrate the occurrence of the use of medicinal plants in Quilombo communities in western Pará, and thus make a relationship with the cultural habits of the community and its collective health.